Employee experience and the phenomenon of “quiet commitment”: When employees engage in silence. A study of enterprises in Hanoi, Vietnam - Minh, Nguyen Van; Thu, Pham Thi (Edelweiss Applied Science and Technology, 2025)
This study investigates Quiet Commitment (QC), a silent yet enduring form of organizational commitment, and develops an integrated model linking Employee Experience (EX), Relational Energy (ERE), Work Meaningfulness (WM), Psychological Safety (PS), and key employee outcomes. Using data from 520 employees working in enterprises across Hanoi, Vietnam, the study applies PLS-SEM to validate measurement scales and examine structural relationships. Results show that EX strongly predicts ERE, and ERE is the most influential antecedent of QC. QC, in turn, significantly enhances in-role performance and reduces turnover intention, while exerting only a modest effect on voice behavior. WM has a substantial direct impact on QC, whereas the moderating roles of WM*ERE and PS*QC are not statistically significant. The findings confirm QC as an independent construct that reflects culturally embedded patterns of modest, action-oriented commitment commonly observed in Vietnamese and broader East Asian work contexts. This study contributes theoretically by conceptualizing QC as a distinct form of commitment and empirically by clarifying the psychological mechanisms through which employee experiences translate into silent but enduring dedication. Managerial implications highlight the importance of building positive employee experiences, fostering relational energy, enhancing work meaningfulness, and designing HR systems aligned with cultural characteristics.